Avances de la globalización y nueva dinámica metropolitana: Santiago de Chile, 1975-1995 - De Mattos, Carlos A (Revista EURE - Revista de Estudios Urbano Regionales, 1996)
This paper has the purpose to analyze the territorial changes produced in Chile since the middle 70Í€™s as a consequence of the implementation of a radical new macroeconomic strategy of economic liberalization. The latter, drastically modified the basic criteria that had guided previously urban and territorial policies. The analysis of the impacts of this policies on the national territorial structure -and, in particular, on its main metropolitan area- are studied considering the two phases of the emerging process of restructuring and globalization. This study concludes that while in the first phase it took place a certain territorial deployment of the productive activities and the population, in the second phase, the secular tendencies to territorial concentration were reestablished and intensified, in the context of a strongly polarized national configuration. For this last phase, the available empiric evidence about the locational territorial preferences of most the new secondary and tertiary activities, shows a proclivity to concentration in the main metropolitan region. This, this new stage of polarization, presents as one of its most relevant features, the steady growth of the urban sprawl around Santiago, marked by an uncontrolled process of suburbanization.